Examining The Zakah Measurement Standards in Indonesia: A Comparative Study Between PSAK (No. 109) and AAOIFI FAS (No. 9) - Nurlia, Nurlia; Anwari, M. Khairul (Universitas Muhammadiyah Pontianak, 2023)
This article aims to examine the accounting treatments for corporate zakat as advocated by accounting rules and recommendations, as well as those used by relevant corporations. The goal is to verify their appropriateness and conformance to both Islamic and accounting theoretical perspectives. Accounting standards and recommendations relating to zakat are studied, including PSAK No. 109 and Financial Accounting Standard No. 9. Furthermore, research on Islamic financial institutions' actions is conducted to determine adherence to both standards and ontological components of zakat. This study demonstrates that there is a common misunderstanding of zakat, as demonstrated by numerous standards and guidelines, which has resulted in inappropriateness in their urged corporate zakat recognition and measurement, and presentation. These beliefs have opposed the true spirit of zakat in Islam in some way. Worryingly, some negative consequences may develop and have already been implicated in the Muslim community as a whole. The study's limitations and implications: This study gives an alternative viewpoint on the accounting treatment of corporate zakat with the purpose of giving a more accurate and fair assessment of zakat on corporate wealth that is more in line with the true spirit of zakat. Uniqueness and worth: The study blends both revealed and modern accounting knowledge in evaluating the standards and practices and presenting an improved and meaningful alternative.